Exploring the role of morphology in the evolution of Spanish - Rini, Joel. (Amsterdam ; Philadelphia : John Benjamins Pub., 1999)
After a brief survey of the perception of morphological change in the standard works of the Hispanic tradition in the 20th century, the author first attempts to refine concepts such as analogy, leveling, blending, contamination, etc. as they have been applied to Spanish. He then revisits difficult problems of Spanish historical grammar and explores the extent to which various types of morphological processes may have operated in a given change. Selected problems are examined in light of abundant textual evidence. Some include: the resistance to change of Sp. dormir 'to sleep', morir 'to die'.
EXPLORING THE ROLE OF MORPHOLOGY IN THE EVOLUTION OF SPANISH; Editorial Page; Title Page; LCC Data; Dedication; Table of Contents; Acknowledgments; Preface; Some Notes About the Present Book; CHAPTER 1. Concepts of Morphological Change: Past and Present; CHAPTER 2. The Nature of Leveling in the Old Spanish Verbal Paradigm; CHAPTER 3. Phonological or Morphological Change?; CHAPTER 4. The Morphological Spread of Sound Change: The Reduction of Old Spanish "-ades, -edes, -ides, -odes"; CHAPTER 5. Hidden Morphological Factors in Apparent Syntactic Change; Conclusion; References; Index of Subjects.
Includes bibliographical references (pages 177-184) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Spanish language -- Grammar, Historical; Spanish language -- Morphology; Espagnol (Langue) -- Grammaire historique; Espagnol (Langue) -- Morphologie; Spanish language -- Grammar, Historical; Spanish language -- Morphology; Diachronische morfologie; Historische grammatica; Spaans; Electronic book